Preparation and Characterisation of a Bis‐μ‐Hydroxo‐NiIII2 Complex - McDonald, Aidan; Spedalotto, Giuseppe; Gericke, Robert; Lovisari, Marta; Farquhar, Erik R.; Twamley, Brendan (My University, 2019)
Hydroxide‐bridged high‐valent oxidants have been implicated as the active oxidants in methane monooxygenases and other oxidases that employ bimetallic clusters in their active site. To understand the properties of such species, bis‐μ‐hydroxo‐NiII2 complex (1) supported by a new dicarboxamidate ligand (N,N′‐bis(2,6‐dimethyl‐phenyl)‐2,2‐dimethylmalonamide) was prepared. Complex 1 contained a diamond core made up of two NiII ions and two bridging hydroxide ligands. Titration of the 1 e− oxidant (NH4)2[CeIV(NO3)6] with 1 at −45 °C showed the formation of the high‐valent species 2 and 3, containing NiIINiIII and NiIII2 diamond cores, respectively, maintaining the bis‐μ‐hydroxide core. Both complexes were characterised using electron paramagnetic resonance, X‐ray absorption, and electronic absorption spectroscopies. Density functional theory computations supported the spectroscopic assignments. Oxidation reactivity studies showed that bis‐μ‐hydroxide‐NiIII2 3 was capable of oxidizing substrates at −45 °C at rates greater than that of the most reactive bis‐μ‐oxo‐NiIII complexes reported to date.
PUBLISHED
Keywords: bis-μ-hydroxo-Ni2; Diamond core; High-valent oxidants; Bioinorganic chemistry; hydrocarbon oxidation